2010
DOI: 10.1111/j.1365-2702.2009.03051.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preoperative fasting on postoperative thirst, hunger and oral intake in paediatric ambulatory tonsillectomy

Abstract: Clinical practice should take the child's perioperative fasting into account in a more accurate way in preoperative counselling of the parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…It was found that the children who had nausea stayed longer in the recovery unit whereas the children who did not have nausea stayed shorter stay in the recovery unit. In the study conducted by Klemetti et al, the frequency and intensity of postoperative nausea and vomiting were not found to be statistically significant between the study group who received nutritional counselling and had a shorter fluid intake time and the control group (33). There was no significant correlation found between the duration of mothers' admission to the recovery unit and agitation and vomiting.…”
Section: Examination Of the Correlation Between Preoperative And Postoperative Conditions Of Childrenmentioning
confidence: 87%
See 1 more Smart Citation
“…It was found that the children who had nausea stayed longer in the recovery unit whereas the children who did not have nausea stayed shorter stay in the recovery unit. In the study conducted by Klemetti et al, the frequency and intensity of postoperative nausea and vomiting were not found to be statistically significant between the study group who received nutritional counselling and had a shorter fluid intake time and the control group (33). There was no significant correlation found between the duration of mothers' admission to the recovery unit and agitation and vomiting.…”
Section: Examination Of the Correlation Between Preoperative And Postoperative Conditions Of Childrenmentioning
confidence: 87%
“…The mean last solid food intake times were similar, whereas the mean fluid intake time was 2.69 (2.08), 1.91/14.35 hours in the study group and 12.13 (2.45), 2.95/14.05 hours in the control group. The difference in the frequency and intensity of postoperative nausea and vomiting between the study and control groups was not statistically significant (33). In the study conducted by Jayasinghe et al in 2018 with 404 children who will undergo bone marrow aspiration, children were divided into two groups randomly; one group fasted for more than 3 hours, and the other group fasted 3 hours.…”
Section: Examination Of the Correlation Between Preoperative And Postoperative Conditions Of Childrenmentioning
confidence: 97%
“…(10) Adicionalmente, quando incentivadas a ingerir líquidos claros até duas horas antes da cirurgia, a criança apresenta menor intensidade de sede durante 24 horas do pós-operatório. (27) Recentes evidências indicam que é seguro para a criança ingerir líquidos claros até mesmo somente uma hora antes de anestesia geral. (20) Esses resultados nos alertam para a necessidade de mudar a prática de jejum prolongado que é realizada em muitas instituições sem evidências científicas, fundamentada em hábitos e rotinas institucionais.…”
Section: Discussionunclassified
“…The parents also graded their children thirst on another similar scale of 0 to 10. 6 Ultrasound examination was performed using a high-frequency (5-10 MHz) ultrasound probe (S-NerveTM; SonoSite Inc) or a curvilinear (2-5 MHz) probe as appropriate, depending on the child weight. Children were scanned in 2 positions: the supine position and the right lateral position (RLP).…”
Section: Methodsmentioning
confidence: 99%